The implementation of the Botswana Technical Education Programme - Mhizha, Bose Margaret (My University, 2013)
A new Vocational Educational Policy, Botswana Technical Education Programme policy (BTEP) has been launched by the Department of Vocational Education and Training to enable the learners to acquire the necessary learning experiences and attributes towards effective preparation for the world of work. The nature of the programme is such that facilitation approaches should be learner-centred. The Quality Assurance policies are aimed to support the implementation of the BTEP. However, they were factors which hindered the effective implementation of BTEP in the Technical Colleges. Consequently, the Colleges implemented the policy partially while there was non-implementation in certain programmes at some Colleges and as a result BTEP failed to increase access in the Technical Colleges as initially intended. This was the research problem of the study. The aim of the study was to explore factors that constrained the implementation of BTEP. The related literature was consulted to determine the changes that could be made to enhance policy implementation. Subsequently, document analysis and semi-structured interviews were used to determine the current BTEP delivery practices of lecturers at four Technical Colleges in Botswana, namely, Maun Technical College, Selebi Phikwe Technical College, Francistown College of Vocational Education and Training and Palapye Technical College. Thereafter, the requirements of the policy and the current practices of the lecturers were compared to determine the factors that had hindered the implementation of BTEP. Though the research identified a number of perceived policy successes, perceived policy failures were also identified as follows: Lack of capacity to implement the policy in the Technical Colleges, lack of support for policy implementation from DTVET, lack of commitment to the policy, diverse interpretation of the policy and lastly negative attitude towards the policy was also identified as a constraining factor. Regarding these perceived constraints it was firstly recommended that DTVET should ensure that there are officers who are held accountable for the progress of the implementation of BTEP at DTVET level. Secondly DTVET should develop strategies to guide and support lecturers to implement BTEP effectively. Furthermore DTVET should ensure that messages are communicated to all stakeholders and that feedback about BTEP is clear and consistent. DTVET should also encourage the Colleges to adopt the policy, mitigate resistance and manage the implementation of BTEP. Lastly DTVET should simplify strategies for implementing the BTEP policy and avoid complex initiatives. This study may provide a solution to the problem of BTEP implementation in the Technical Colleges in Botswana. I write this in particular to advice and encourage, the Department of Vocational Education and Training, Programme Design and Development Unit, Quality Assurance Unit, College Management teams and lecturers to make use of the issues raised in this study to help them improve BTEP implementation in the Technical Colleges.
Thesis (M.M. (Public Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: Technical education; Vocational education; Botswana